Pemahaman Mahasiswa terhadap Protokol Kesehatan di Masa Pandemi Covid-19 - Muhammad Akbar Syafruddin; Muhammad Hasbillah; Charmila Tandru Rerung (Gerak: Journal of Physical Education, Sports, and Health, 2021)
In the current pandemic situation, it is very important for every individual to follow medical procedures to protect themselves from being infected with COVID19. Each individual tends to follow the health protocol or not. This study aims to describe the compliance of students of the STKIP YPUP Makassar Penjaskesrek Study Program in implementing health protocols during the COVID19 pandemic situation. The research was conducted with a descriptive qualitative approach. The instrument used in this research is an open questionnaire and data analysis techniques using encryption. The research sample was taken from the 5th semester students of Penjaskesrek Study Program STKIP YPUP Makassar as many as 35 respondents using random sampling technique. The results of this study indicate that most students have implemented health protocols. However, there are still students who do not follow health service procedures due to a lack of understanding about COVID19.